Driving Employee Experience: The Role of Value Based Organisation Culture - Sainger, Garima (International Journal of Psychosocial Rehabilitation, 2020)
The Research Paper Titled Driving Employee Experience: The role of value based organisation Culture is a conceptual paper based on extensive review of various survey reports on aspects related to Employee experience at work and organisation. In the paper theoretical description about concept and evolution of employee experience discussed in the beginning and define it as employees’ employment journey about, what he feels, and observe at an organisation. The study also explains different benefits organisations entertain with positive employee experience. On the basis of reviews of different survey reports drivers of employee experience has been discussed. The paper also discusses that these drivers also influenced by overall organizational culture. Culture is a set of values, behaviours and tools that provide structure, and employee experience is what happens at the intersection of individual personality and organisational culture. The values organisation practices are the most important aspect of its culture and also serves as basis of employee experience.The paper further discusses that to develop organisation culture eight dimensions of the OCTAPACE values need to be examined. If culture follows OCTAPACE values, it can result Dimensions of employee experience index and fulfilment of all these dimensions is the basic requirement of improved employee experience. At the end of the paper conclusions drawing importance of overall study has been discussed. On the whole the research paper shall prove useful for showing importance of positive employee experience for organisation performance in the light of value based organisation culture.